INFLUENCE OF RAINFALL AND TEMPERATURE VARIATION AMONGST MALARIA DIAGNOSED ENROLLEES OF NATIONAL HEALTH INSURANCE SCHEME, AHMADU BELLO UNIVERSITY, ZARIA, NIGERIA - Ekpo, Regina; Abaje, Iliya B.; Oloko, M.; Laah, J. G. (FUDMA JOURNAL OF SCIENCES, 2020)
The occurrence and frequency of malaria in humans has been attributed to climate change due to change in human activities over the years.  The paper assessed the influence of temperature and rainfall variation on malaria diagnosed enrollees of NHIS in Ahmadu Bello University, Zaria. Temperature and rainfall data and malaria prevalence for the period of 2008-2017 were analyzed. Second order polynomial curve fitting was used to determine the non-linear trends of temperature, rainfall and malaria cases. Its relationship was tested using Pearsonâ€™s product moment correlation coefficient. The result revealed that an upward trend in temperature and rainfall is capable of increasing the occurrence of malaria in the study area. There is a strong relationship between the number of malaria diagnosed enrollees of NHIS and the change in temperature and rainfall. It is recommended that there is need for proper environmental sanitation and more awareness on the need to use insecticide treated nets (ITN) to prevent mosquito bites. Also, proper budget on malaria for both enrollees should be made increased during the rainy season than the dry season in order to checkmate the challenges derived from variation in temperature and rainfall on individualâ€™s health.